Retention of HIV exposed infants in care at Arua regional referral hospital, Uganda: a retrospective cohort study - Pontius Apangu; Jonathan Izudi; Francis Bajunirwe; Edgar Mulogo; Vincent Batwala (BMC, 2019)
Abstract Background Retention of HIV Exposed Infants (HEIs) in care ensures adequate care. Data on retention of HEIs at large referral hospitals in Uganda is limited. We investigated the retention level of HEIs and associated factors. Methods We conducted a retrospective cohort study on 352 HEIs in care (January 2014 and April 2015) at Arua Regional Referral Hospital, North-western Uganda. Electronic medical data were retrieved and analyzed with Stata. Chi-square, Fisher's exact, and Students t-tests were used for bivariate analysis. Logistic regression was performed to determine factors independently associated with retention. Results 236 (67.0%) HEIs were delivered in a health facility and 306 (86.9%) received Nevirapine prophylaxis from birth until 6-weeks. Of mothers, 270 (76.7%) were 25-46 years, 202 (57.4%) attended antenatal care (ANC) at recent pregnancy, and 328 (93.2%) were on life-long anti-retroviral therapy. At 18-months, 277 (78.7%) HEIs were retained in care. Maternal age (25-46 years) (Adjusted Odds Ratio (AOR), 2.32; 95% CI, 1.32-4.06), ANC attendance during recent pregnancy (AOR, 2.01; 95% CI, 1.19-4.3.41) and Nevirapine prophylaxis initiation from birth until 6-weeks (AOR, 3.07; 95% CI, 1.50-6.26) were associated with retention. Conclusion Retention was suboptimal. Older maternal age, ANC visits at last pregnancy, and timely NVP initiation increased retention.